SCFFbxw5 mediates transient degradation of actin remodeler Eps8 to allow proper mitotic progression - Werner, Achim; Reifenberger, Nina; Habeck, Gregor; Becker, Janina; Lorenz, Holger; Melchior, Frauke (Nature cell biology, 2013)
Eps8, a bi-functional actin cytoskeleton remodeler, is a positive regulator of cell proliferation and motility. Here, we describe an unrecognized mechanism regulating Eps8 that is required for proper mitotic progression: While Eps8 is stable in G1 and S phase, its half-life drops sharply in G2. This requires G2-specific proteasomal degradation mediated by the Ubiquitin E3 ligase SCFFbxw5. Consistent with a short window of degradation, Eps8 disappears from the cell cortex early in mitosis, but reappears at the midzone of dividing cells. Failure to reduce Eps8 levels in G2 prolongs its localization at the cell cortex and markedly delays cell rounding and prometaphase duration. However, during late stages of mitosis and cytokinesis, Eps8 capping activity is required to prevent membrane blebbing and cell shape deformations. Our findings identify SCFFbxw5-driven fluctuation of Eps8 levels as an important mechanism that contributes to cell-shape changes during entry into - and exit from - mitosis.
"Fbxw5" erscheint kleiner gedruckt und hochgestellt
Gesehen am 27.11.2018